Cognitive dissonance resolution is related to episodic memory. - Moti Salti (Public Library of Science (PLoS), 2014)
The notion that our past choices affect our future behavior is certainly one of the most influential concepts of social psychology since its first experimental report in the 50 s, and its initial theorization by Festinger within the "cognitive dissonance" framework. Using the free choice paradigm (FCP), it was shown that choosing between two similarly rated items made subjects reevaluate the chosen items as more attractive and the rejected items as less attractive. However, in 2010 a major work by Chen and Risen revealed a severe statistical flaw casting doubt on most previous studies. Izuma and colleagues (2010) supplemented the traditional FCP with original control conditions and concluded that the effect observed could not be solely attributed to this methodological flaw. In the present work we aimed at establishing the existence of genuine choice-induced preference change and characterizing this effect. To do so, we replicated Izuma et al.' study and added a new important control condition which was absent from the original study. Moreover, we added a memory test in order to measure the possible relation between episodic memory of choices and observed behavioral effects. In two experiments we provide experimental evidence supporting genuine choice-induced preference change obtained with FCP. We also contribute to the understanding of the phenomenon by showing that choice-induced preference change effects are strongly correlated with episodic memory.